LU Filoloģijas un filozofijas fakultātes bibliotēkas krājuma veidošanās pirmskara periodā - Mantiniece, Ilga (Latvijas Universitāte, 2017)
Jaunveidotās Latvijas Augstskolas humanitārajās fakultātēs nodaļu bibliotēku krājumi bija jāveido no pamatiem. Filoloģijas un filozofijas fakultātes bibliotēkai grāmatas tika iegūtas, gan ar valsts piešķīruma, gan pirkumu, gan dāvinājumu palīdzību, no 350 grāmatām 1919. gadā līdz vairāk nekā 40 tūkstošiem 1939. gadā. Rakstā skatīti galvenokārt krājuma veidošanās pirmie gadi.
Formation of Library Holdings at the UL Faculty of Philology and Philosophy during the Pre-war Period
The faculties of the humanities of the newly established University of Latvia had to create their libraries from the ground up, as opposed to the technical libraries who had partly preserved the stocks from the departments of the predecessor, the RPI. Books for the library of the Faculty of Philology and Philosophy were obtained through governmental allocations, purchases, and donations, and so it grew from 350 books in 1919 to more than 40 thousand in 1939. This article explores the first years of the formation of library holdings.
Keywords: Research Subject Categories::SOCIAL SCIENCES::Other social sciences::Library and information science; Filoloģijas un filozofijas fakultātes bibliotēka; Latvijas Universitāte; Library of the Faculty of Philology and Philosophy; University of Latvia; Bibliotēkas krājuma veidošanās; Izdevumu ieguves avoti; Formation of library holdings; History of the University of Latvia; Latvijas Universitātes vēsture; Book acquisition